Density management diagrams in mixed and uneven-aged forests of Durango, México - Corral-Rivas, Sacramento; Álvarez-González, Juan G; Corral-Rivas, José J; Wehenkel, Christian; López-Sánchez, Carlos A (Bosque (Valdivia), 2017)
Density management diagrams (DMD) are graphical tools used in the design of silvicultural regimes for both even-aged and uneven-aged forests. They depict the relationship among stand density, average tree size, stand yield and dominant height, based upon relevant ecological and allometric relationships such as the self-thinning rule, the yield-density effect, and site index curves. DMD effectively summarize stand structural descriptors, and are therefore helpful in determining stand characteristics needed to achieve a range of management goals. In this work several DMD were built for conifer and broadleaf species in two conditions of productivity in mixed and uneven-aged forests in Northwest of Durango, Mexico. Additionally, two DMD were developed including all species present in the stand (conifer + broadleaves) for each level of productivity and finally a DMD as the sum of the two levels of productivity for all species into stand was developed. We used 15,360 temporal sample plots from a region-wide forest inventory. To determine the maximum density isoline we selected 333 plots with maximum density (considering the group of species belonging to conifers). Site index curves were used to assess the time taken by stands to progress along their development trajectories. The DMD of species grouped into conifers in high productivity level was used as a case study to illustrate how the diagram can be used to assess current functionality of the forest, forecast its likely development and compare alternative management strategies.